Choosing in Freedom or Forced to Choose? Introspective Blindness to Psychological Forcing in Stage-Magic - Shalóm, Diego Edgar (2013)
We investigated an individual ability to identify whether choices were made freely or forced by external parameters. We capitalized on magical setups where the notion of psychological forcing constitutes a well trodden path. In live stage magic, a magician guessed cards from spectators while inquiring how freely they thought they had made the choice. Our data showed a marked blindness in the introspection of free choice. Spectators assigned comparable ratings when choosing the card that the magician deliberately forced them compared to any other card, even in classical forcing, where the magician literally handles a card to the participant This observation was paralleled by a laboratory experiment where we observed modest changes in subjective reports by factors with drastic effect in choice. Pupil dilatation, which is known to tag slow cognitive events related to memory and attention, constitutes an efficient fingerprint to index subjective and objective aspects of choice.